Giardia intestinalis can interact, change its shape and internalize large particles and microorganisms. Issue 4 (7th April 2021) - Benchimol, Marlene
Abstract: Giardia intestinalis is a parasitic protozoan that inhabits its vertebrate hosts' upper small intestine and is the most common cause of waterborne diarrhoea worldwide. Giardia trophozoites present few organelles, and among them, they possess peripheral vesicles (PVs), which are considered an endosomal–lysosomal system. All experimental procedures carried out until now indicate that Giardia ingests macromolecules by fluid-phase and receptor-mediated endocytic pathways. Still, there is no description concerning the interaction and ingestion of large materials. Here, we tested Giardia 's capacity to interact with large particles; once, in vivo, it inhabits an environment with a microbiota. We tested protozoan interaction with yeasts, bacteria, latex beads, ferritin and albumin, in different times of interaction and used several microscopy techniques (light microscopy, scanning electron microscopy and transmission electron microscopy) to follow their fate. Giardia interacted with all of the materials we tested. Projections of the plasma membrane similar to pseudopods were seen. As albumin, small markers were found in the PVs while the larger materials were not seen there. Large vacuoles containing large latex beads were detected intracellularly. Thus, we observed that: (1) Giardia interacts with large materials; (2) Giardia can display an amoeboid shape and exhibit membrane projections when in contact with microorganisms and large inorganic materials; (3) the region of the exit of the ventral flagella is very active when in contact with large materials, although all cell surface also present activity in the interactions; (4) intracellular vacuoles, which are not the PVs, present ingested large beads.